A drivers exposure to traffic pollution - Clarke, Robert (1998)
The increasing use of road transport in the post war years has caused a substantial rise in the amounts of traffic related air pollutants and has raised concerns about urban air quality. This thesis describes a series of experiments designed to evaluate the level of traffic pollutants experienced by drivers in heavy traffic.